Pengembangan Bahan Ajar Google Slide Pada Mata Pelajaran IPA Kelas V MI/SD - Norliana, Norliana; Syar, Nur Inayah; Sulistyowati, Sulistyowati (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2023)
The use of teaching materials that are limited to textbooks and surrounding objects, as well as the complexity of materials that contain important terms can hinder the achievement of learning objectives. The development of teaching materials based on Google Slides can overcome the limitations of the material and help the process of understanding the material. This study aims to develop teaching materials based on Google Slides for science subjects in class V MI/SD. This study uses the R&D (research and development) method with the 4D development model, namely: define, design, develop, and disseminate. Data collection techniques through observation, interviews, questionnaires and documentation. The study resulted in the development of Google Slides teaching materials for the science subject on the water cycle. The results of the product assessment show that the feasibility assessment by material experts in the final stage obtained a feasibility percentage with a score of 90.6% including the